Bioremediation of hydrocarbon-contaminated soils in cold regions: Development of a pre-optimized biostimulation biopile-scale field assay in Antarctica - Martinez Alvarez, Lucas Manuel; Ruberto, Lucas Adolfo Mauro; Lo Balbo Alfredo; Mac Cormack, Walter Patricio (Science of The Total Environment)
Bioremediation proved to be an effective approach to deal with soil contamination, especially in isolated, cold environments such as Antarctica. Biostimulation, involving the addition of macronutrients -mainly nitrogen and phosphorous- is considered the simplest and cheapest bioremediation process. Optimizing the levels of these nutrients is a key step prior to the application of a biostimulation strategy. In this work, N and P levels, optimized by Response Surface Methodology (RSM) at lab-scale, were applied to an Antarctic hydrocarbon contaminated soil. The process was performed on-site, using high density polyethylene geomembranes (800 μm) to isolate treated soil from the surroundings and under environmental conditions at Carlini station (Antarctica) during 50 days. Two 0.5 ton biopiles were used as experimental units; a control biopile (CC), and a biostimulated system (BS), amended with N and P. At the end of the assay, hydrocarbon removal was significantly higher in BS system compared to CC (75.79% and 49.54% respectively), showing that the applied strategy was effective enough to perform a field-assay in Antarctica that significantly reduce soil contamination levels; and proving that RSM represents a fundamental tool for the optimization of nutrient levels to apply during bioremediation of fuel contaminated cold soils. Fil: Martinez Alvarez, Lucas Manuel. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Ruberto, Lucas Adolfo Mauro. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Houssay. Instituto de Nanobiotecnología. Universidad de Buenos Aires. Facultad de Farmacia y Bioquímica. Instituto de Nanobiotecnología; Argentina Fil: Lo Balbo Alfredo. Universidad de Buenos Aires; Argentina Fil: Mac Cormack, Walter Patricio. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina